SYNTHESIS, CHARACTERIZATION AND ANTHELMINTIC ACTIVITY (PERITUMA- POSTHUMA) OF FLUORO SUBSTITUTED BENZOTHIAZOLE FOR BIOLOGICAL AND PHARMACOLOGICAL SCREENING. - VIJAYA JAVALI; JAYACHANDRAN E; RAVI SHAH; KALPESH PATEL; SREENIVASA G.M. (International Journal of Pharma and Bio Sciences, 2010)
Various substituted 7-chloro-6-fluoro-N-(1,3-thiazol-2-yl)-1,3 benzothiazol-2-amine 1-(7-chloro-6-fluoro1,3-benzothiazol-2-yl) thiaourea containing different functional groups have been synthesized by condensing Chloroacetyl chloride with 2-aminobenzothiazole in Ammonium thiocyanate/Hcl The synthesized compounds was identify were confirmed on the basis of their spectral (UV-VIS, IR, 1HNMR and MASS) data. All the compounds have been screened for their antibacterial activity.